Perlindungan Hukum terhadap Pekerja Rumah Tangga di Indonesia: Studi Literatur Implementasi UU No. 13 Tahun 2003 & Konvensi ILO No. 189 - Nikmah Dalimunthe; Rahmah Aliyah (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This research aims to examine the gap in legal protection for domestic workers in Indonesia through an analysis of Law No. 13 of 2003 on Manpower and ILO Convention No. 189 on Decent Work for Domestic Workers. Until now, domestic workers have not been explicitly recognized in national regulations, so their basic rights such as living wages, social security, and humane working hours are often neglected. This condition is exacerbated by the absence of written work contracts, the dominance of informal recruitment, and the view of the community that does not consider domestic workers as formal workers. This article concludes that the ratification of ILO Convention 189 and the passing of the Domestic Workers Protection Bill are strategic steps to strengthen legal protection for domestic workers in Indonesia, which also needs to be supported by labor inspection and comprehensive legal education.